Pertanggungjawaban Pidana Aparat Kepolisian Yang Melakukan Kekerasan Terhadap Demonstran - Dames Lewansorna; Elsa Rina Maya Toule; Margie Gladies Sopacua (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: The demonstration, which was held by the Indonesian Christian Student Movement (GMKI) Ambon Branch, demanded the Maluku Provincial Government and the Maluku Provincial People's Representative Council (DPRD) to legalize the traditional Sopi drink, but the action that was held ended in chaos due to actions taken by the authorities. the police against student actions by ignoring and paying attention to the rights of the demonstrators so that it deserves a serious response because the actions of the police have deviated from the provisions of legislation Number 2 of 2002 concerning the Republic of Indonesia Police Article 2, 13 and 14 paragraph 1 letter e, as well as the 1945 Constitution Article 30 paragraph 2. Therefore, it is appropriate to question the existence of the Indonesian National Police apparatus who violates the provisions of laws and regulations and must be held criminally responsible.Purposes of the Research: Explain about how the criminal responsibility of police officers who commit violence against demonstrators. Methods of the Research: The type of research used is normative juridical research. The approach to the problem used is a statutory approach that prioritizes legal materials and a case approach.Results of the Research: Criminal liability is a form of accountability due to mistakes made by legal subjects. In essence, criminal liability is a mechanism built by criminal law to react to an agreement to reject a certain act. Police as legal subjects in their existence are human beings, who are also given legal rights and obligations (fictie theory). According to the Geen Straf Zonder Schuld principle; Actus non facti reum nisi mens sis sist rea is basically a person who cannot be convicted if there are no mistakes, so observing the above based on the examples of cases that have been discussed in the previous chapter regarding cases of violence committed by Akp Syarifudin, the position of the Head of the Sabara Unit of the Island Police. Ambon and the Lease Islands have been transferred to other places of assignment for committing acts of violence against several members of the Ambon Branch GMKI and damaging the goods (kordon) of the Ambon branch of GMKI. The criminal can be punished on the basis of error. if seen from the case study of the position above his subordinates, what Syarifudin did as the Head of the Sabara Unit, was included in the category of acts of violence regulated in Article 170 of the Criminal Code.